PFKFB3 potentially contributes to paclitaxel resistance in breast cancer cells through TLR4 activation by stimulating lactate production - Ge, X; Cao, Z; Gu, Y; Wang, F; Li, J; Han, M; Xia, W; Yu, Z; Lyu, P (Cellular and Molecular Biology, 2016)
Paclitaxel is a commonly used agent for breast cancer therapy, which comes across the obstacle "drug resistance”, resulting in shortened overall survival of patients. Warburg effect has become one character of cancer cell and was reported to induce paclitaxel resistance, the mechanism of which is poorly understood. In this study, we sought to examine the role of 6-Phosphofructo-2-kinase (PFKFB3), a critical regulator of glycolysis, in paclitaxel resistance development. Two clones of paclitaxel resistant breast cancer cells, MCF-7RA and MCF-7RB, were established by a long term exposure of MCF-7 cells to paclitaxel. Consequently, PFKFB3 expression was found to be increased in MCF-7RA and MCF-7RB cells compared with MCF-7 cells. Silencing PFKFB3 expression markedly reduced the IC50 concentrations of MCF-7RA and MCF-7RB cells. Moreover, PFKFB3 modulated toll like receptor 4 (TLR4) and MyD88 expression as well as interleukin (IL)-6 and IL-8 release from breast cancer cells in response to paclitaxel exposure. In addition, PFKFB3 overexpression boosted up fructose-2,6-bisphosphate (F2,6BP) and lactate production. The enhanced lactate contributed to TLR4 signaling activation, IL-6 and IL-8 generation, and cell viability promotion in MCF-7 cells. In all, we characterized the novel role of PFKFB3 in induction of paclitaxel resistance by raising lactate production and activating TLR4 signaling.